2014
DOI: 10.3171/2014.2.spine13800
|View full text |Cite
|
Sign up to set email alerts
|

Repeated adjacent-segment degeneration after posterior lumbar interbody fusion

Abstract: One of the most important sequelae affecting long-term results is adjacent-segment degeneration (ASD) after posterior lumbar interbody fusion (PLIF). Although several reports have described the incidence rate, there have been no reports of repeated ASD. The purpose of this report was to describe 1 case of repeated ASD after PLIF. A 62-year-old woman with L-4 degenerative spondylolisthesis underwent PLIF at L4–5. At the second operation, L3–4 PLIF was performed for L-3 degenerative spondylolisthesis 6 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Paul Park [21] reported a high incidence of ASD after PLIF surgery. According to two other studies, the incidence even reached 100% [22]. Shinya Okuda [22] reported a case of repeated ASD after PLIF in which the patient had four times of operation at different adjacent lumbar segments.…”
Section: Discussionmentioning
confidence: 97%
“…Paul Park [21] reported a high incidence of ASD after PLIF surgery. According to two other studies, the incidence even reached 100% [22]. Shinya Okuda [22] reported a case of repeated ASD after PLIF in which the patient had four times of operation at different adjacent lumbar segments.…”
Section: Discussionmentioning
confidence: 97%
“…Compared with the traditional technique, the screws and rods can be instrumented and assembled through small hole-like wounds which could cause less injury to the paraspinal soft tissue structures. Whether traditional or MISS technique is adopted, however, the metallic fixation inevitably induces kinematic and kinetic compensation from the instrumented to adjacent segments (Kwon et al, 2013;Lawrence et al, 2012;Lee et al, 2014;Lu et al, 2015;Nakashima et al, 2015;Okuda et al, 2014). Using static rather than dynamic fixation, the current authors have not yet found enough literature report to reveal an effective technique to mitigate the ASD progression.…”
Section: Introductionmentioning
confidence: 88%
“…However, the rigidity-raising effect, resulting from interbody fusion and transpedicular fixation, potentially induces adjacent segment disease (ASD) problems that accelerate the degeneration of the adjacent discs and facet joints (Kwon et al, 2013;Lawrence et al, 2012;Lee et al, 2014;Nakashima et al, 2015). Such an instrumentation-induced problem has been attributed to the fact that the constrained mobility and loads of the instrumented segments is compensated for by the adjacent segments (Lu et al, 2015;Okuda et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…ASD has been previously examined with a review of earlier reports 19,20) . Previous reports had ASD rates ranging from 1.4% to 18.5% [19][20][21][22][23][24][25][26][27][28][29] . In the present series, all ASD patients without residual motor loss or multiple revision surgery at the same segment experienced improvement in their deteriorated symptoms after revision surgeries; furthermore, both patient-and surgeonbased surgical outcomes were almost equal in patients without ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Although many reports have described the surgical outcomes of PLIF [1][2][3][19][20][21][22][23][24][25] , there have been no patient-based satisfaction analyses of PLIF. Patient-based surgical outcomes of PLIF for lumbar spondylolisthesis were previously reported for the first time 15,16) .…”
Section: Discussionmentioning
confidence: 99%